Teknik dan Taktik Pembelajaran Tari Kreasi Bakul Melalui Metode Kerja Kelompok pada Siswa Kelas XI IPA 2 di SMA Negeri 11 Palembang - Andriani, Andriani; Elvandari, Efita; Hidayatullah, Fadhilah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to describe the techniques and tactics of learning basket dancecreations through group work methods for students of class XI IPA 2 at SMA Negeri 11 Palembang. The focus of the research is on learning basketry dance creations using the group work method. While the sub-focus of this research is the techniques and tactics through the group work method in learning the creation of bakul dance for class XI science 2. The research problem is how are the techniques and tactics for learning the basket dance through the group work method for students of class XI science 2. The method used in this study is a qualitative method. The samples of this study were students of class XI IPA 2. The data collection techniques used in this study were observation, interviews, and documentation. the value of 86 from the value of 86-100 with the criteria of